Understanding Society Perception About Giving Respond Toward Hijabers Community - Mei Indriyani, Risti; Budi Lestari, SU, Dr. Dra. Sri (Interaksi Online, 2016)
Perception requires an object to be perceived. Each person has different thought on the reality that surrounds them. Hijabers community is one of the social perception object which perceive variously by the society. In the community activity, they do many positive activities according the Islamic rules, and pursuade Moslem women to wear fashionable hijab. But, those activities didn‟t get any good respond or well perceived by the society. Yet there is some people who has negative perception toward this community. This research aims to describe how society perceive the Hijabers Community members‟ behaviour in their daily life using descriptive qualitative method with phenomenology analysis. The theories that used are the symbolic interaction theory which is a reference framework to understand how human create the symbolic world and how they create behaviour, and the perception theory which explains how human catch the stimulus that influence the human sense. In this research, it is found that: The stimulus‟ shape that received by the informants depend on their intepretation of symbol – which is the message that inteprets based on the mutual agreement. From the research result, it is found that the most stand out symbol in Hijabers Community which is understood by the society is the outfit. The stimulus which has been received by the informants then will create a perception towards Hijabers Community. Society‟s perception toward Hijabers Community is various, depends on the received stimulus and the motive or needs to these stimulus. The result from this research is that not all informants have negative perception which describes Hijabers Community as a community that concerns only on their fashionable clothes, but they tend to think Hijabers Community as a positive community seen from their activities. Meanwhile, negative perception is owned by the informant who has negative experience toward this community. The negative experience is in the form of society‟s negative comments and seeing the community appearance which is obtained from the received stimulus by the informant about the things that make the informant perceived Hijabers Community as a community which concerns about the appearance rather than religion matters